Pathophysiological significance of creatinekinase and lactatedehydrogenase in the mechanisms of adaptation of muscle tissue of descendants - G. Stepanov (Journal of Education, Health and Sport, 2023)
Over the past half century, the human population has seen a significant increase in the proportion of individuals exposed to ionizing radiation. One of the urgent problems of radiobiology is the establishment of the natural radiosensitivity of the organism, which provides the possibility of predicting the remote consequences of radiation exposure. The general condition of animals after ionizing radiation and the changes caused by this radiation largely determine the functioning of muscle tissue, which plays an important role in ensuring the vital activity of the body. The leading pathogenetic factor of radiation damage to the body is a violation of the metabolism and structural organization of enzymatic systems, due to which a sequence of biochemical processes and compartmentalization of enzyme systems change, and their solubilization increases. Additionally, it is extremely important to understand the detailed mechanisms of energy supply for the functioning of muscle tissue in the body of intact animals. The purpose of the work is to determine the pathophysiological significance of creatinekinase and lactatedehydrogenase in the mechanisms of adaptation of the body of the descendants of intact rats to the influence of a stress factor by studying changes in the activity of creatinekinase and lactatedehydrogenase in the blood and muscle system. A characteristic feature of creatine metabolism in 1-month-old pup rats was shown to be the low content of creatine and creatinine in skeletal and cardiac muscles against the background of low activity of the creatine phosphokinase enzyme in these muscles and its sharp increase in blood. Expressed hypercreatinuria and hypocreatininuria are registered in the blood of 1-month-old pup rats, which can be realized due to the strengthening of biosynthetic processes against the background of the inability of muscle tissue to fix these metabolites. In the skeletal and cardiac muscles of intact 1-month-old pup rats, the activity of creatine phosphokinase is decreased due to the decrease in the activity of the MM -isoform of the enzyme. The investigated metabolic processes in the muscle system of intact animals were shown to be extremely sensitive to the altering influence of ionizing radiation. The authors stressed that understanding the pathophysiological mechanisms of adaptation of the muscular system to the probable influence of a stressful radiation factor, we can draw a conclusion about the depth and severity of the pathological process based on the state of the enzyme systems, and we consider the determination of enzymatic tests in the blood to be important in diagnostic and prognostic aspects.